Performance of the neutrophil-to-lymphocyte ratio as a prognostic tool for survival in solid cancers - Carrión-Barberà, Irene; Lood, Christian (Frontiers in Oncology, 2025)
Neutrophils and lymphocytes are crucial players in cancer progression, with the neutrophil-to-lymphocyte ratio (NLR) emerging as a potential prognostic biomarker. However, its clinical relevance remains uncertain. This study retrospectively analyzed individual patient data from five Phase III clinical trials encompassing multiple cancer types to assess the prognostic value of baseline neutrophil (N1), lymphocyte (L1), and NLR (NLR1) counts for overall survival (OS) and progression-free survival (PFS). Survival outcomes were evaluated using Kaplan-Meier analyses, Cox proportional hazards models, and receiver operating characteristic curves, with subgroup analyses conducted across demographic and clinical subpopulations. High NLR1 and N1 and low L1 were associated with worse OS and PFS. In Cox uni- and multivariate analyses, NLR1 was an independent predictor of OS (HR: 1.508 (95% CI: 1.390 – 1.636, p<0.001)), while N1 and L1 were only significant when analyzed categorically (N1 HR: 1.390, L1 HR: 0.801; all p < 0.001). Similar patterns were observed for PFS (NLR1 HR: 1.261, N1 HR: 1.154, L1 HR: 0.848; all p < 0.001). Biomarkers showed higher HR in < 60 years, Non-White, Stage IV, and Eastern Cooperative Oncology Group Performance Status = 1 patients. Kaplan-Meier analysis confirmed worse survival for most patients with highest NLR1 or N1 and low L1 and low L. These findings confirm the prognostic role of blood cell components in cancer risk assessment and underscore the importance of personalized biomarker-based stratification, warranting further prospective studies to establish standardized clinical use.